THEORY OF COGNITIVE AND CONCEPTUAL METAPHORS (Scientific journal of the Fergana State University, 2024)
This article explores the theory of cognitive and conceptual metaphors, emphasizing their significance in shaping human thought and language. Conceptual metaphor theory, primarily developed by Lakoff and Johnson, posits that metaphors are fundamental to human cognition, not merely linguistic expressions. This study examines the cognitive processes underlying metaphorical thinking and their implications for language, culture, and communication. Using a mixed-methods approach, the research integrates quantitative analysis of metaphor usage across different languages and qualitative insights from cognitive linguistics. The findings reveal the pervasive nature of conceptual metaphors in everyday language and their role in structuring abstract concepts through concrete experiences.